The Effectiveness of an Outdoor Training Programme at Banseke Human Resource Development Centre - Lau, Yin Yin (2001)
This study was conducted with the objective to evaluate the effectiveness of an experiential-training-approach using the realities of outdoors activities, conducted by Banseke Human Resource Development Centre. This study employed the four levels of the Kirkpatrick Model, focusing on the reaction and learning levels. To date, more than 4000 people have attended courses conducted by Banseke using this approach. Generally, the majority of the participants have declared that the modules have been effective and have helped them. The participants who have undergone Banseke's Corporate Wargame courses felt that the modules and courses offered were very innovative and unique. However, a reliable academic evaluation of the effectiveness of these courses has never been carried out because of the considerable time and effort required from everyone involved, until this research was conducted. This research employed a quantitative approach with utilization of descriptive and inferential research. Sixty-seven participants on two courses participated in this study. Another thirty-six participants became the subjects of the pilot test. During the actual test, the participants were made up of 29% of non-executive level, 40% of junior executive level and 31 % of managerial level. The questionnaires developed were adopted and adapted from Fisher et al. (1999), Francis and Young (1979), Torres and Fairbanks (1996), an unpublished survey done by Banseke (2000), Kirkpatrick (1994) and Daft (1997), using the five-point Likert-type format (1=strongly disagree, 5=strongly agree).